Morphological changes of the thyroid gland as a new radiographic marker for lung cancer treatment efficacy of immune checkpoint inhibitors. (January 2021) - Itonaga, Tomohiro; Saito, Kazuhiro; Ikeda, Norihiko; Mikami, Ryuji
Background: Fully human IgG4 programmed cell death-1 (PD-1) immune checkpoint inhibitors are effective against non-small-cell lung cancer (NSCLC). PD-1-targeted antibodies induce autoimmune adverse events that are not caused by conventional chemotherapy. Purpose: To clarify the association between morphological changes of the thyroid gland and the efficacy of PD-1 immune checkpoint inhibitor treatment for lung cancer. Material and Methods: The study enrolled 29 patients who received PD-1 immune checkpoint inhibitor treatment. The thyroid volume was measured using computed tomography (CT) at the following three timepoints: pre-treatment (baseline); three months after the initial administration (early treatment); and at the last CT scan during the observation period (late treatment). Thyroid volume ratios were calculated as follows: early treatment/baseline thyroid volume at CT (E/B-CT ratio) and late treatment/baseline thyroid volume at CT (L/B-CT ratio). Thyroid dysfunction was assessed according to thyroid hormone levels. Results: The E/B-CT ratio was significantly higher in patients with adverse events of grade 3 or higher than in the other patients ( P  = 0.013). The L/B-CT ratio was significantly lower in patients with thyroid dysfunction than in those without thyroid dysfunction ( P  = 0.001). Complete response (CR) was achieved in three patients at the time of the final CT. The E/B-CT ratio was significantly higher in patients with CR than in the other patients (1.48 vs. 0.99, P  = 0.029). Conclusion: Changes in thyroid volume after administration of PD-1 immune checkpoint inhibitors might be a useful radiographic marker of therapeutic efficacy in patients with lung cancer.